Aspects of the use of artificial intelligence technologies - O. Solntseva (State University of Management, 2019)
Currently, there is an influence of innovation on technological processes in various fields, and the use of artificial intelligence technologies has a direct impact on the development of society. The article investigates the main trends in the development of artificial intelligence, the study revealed that at the moment, the field of artificial intelligence can be considered as a mixture of cognitive Informatics, linguistics, psychology and mathematics. The aspects of the use of artificial intelligence in various spheres of life, such as industry, agriculture, public service, education, banks and Finance, medicine, transport and transport system, household and services are considered. The expediency of the introduction of innovative technologies in various fields, including the future is argued. The possibility of using robots, unmanned objects, drones, intelligent training programs and systems is analyzed. The influence of innovations on technological processes is characterized. The analysis reveals the possible advantages and difficulties of artificial intelligence application. Despite all the possibilities of artificial intelligence technologies, using of it is characterized by errors. It is impossible to completely replace the management potential with artificial intelligence, especially in those areas in which the human factor plays an important role. According to the author, despite all the obvious advantages, artificial intelligence should only help people to make their work even more effective and safe, but in any case not to replace them completely. Technologies, certainly, should develop, but this development should be harmonious with the development of society. The author comes to the conclusion that the training of the machine and its subsequent use depends entirely on the person. The use of artificial intelligence technologies and robotics can make our lives better, and in the future, may be a salvation for humanity.